Haematological Parameters and Oxidative stress Changes in Apparently Healthy Pregnant Women in Pakistan - Muhammad Hassan Saleem, Abdul Rahman Abid, Mussarat Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Pregnancy is associated with alterations in haematological and oxidative stress parameters as physiological adjustments are made to accommodate the increasing demand from the fetus and the maintenance of maternal wellbeing. In this cross-sectional study, baseline values for haematological and oxidative stress changes were evaluated in pregnant women attending an ante-natal clinic at selected private clinics in Lahore. A total of 100 subjects (80 pregnant women and 20 non-pregnant women) were recruited for the study. Haematological and oxidative stress parameters were determined following standard protocols. When comparing pregnant and non-pregnant women’s white blood cell, neutrophil, monocytes, and catalase mean values (p 0.05), it was observed that the pregnant women’s eosinophil mean values were lower than those of the non-pregnant control (p 0.05). During the third trimester, neutrophils and catalase levels were significantly higher in the pregnant group than they were in the non-pregnant group (p 0.05) Compared to catalase, superoxide dismutase was shown to be adversely associated with both mean cell volume and haemoglobin concentration. Other variables studied were mean haemoglobin, mean haemoglobin concentration, total white blood cell and neutrophil counts, and mean cell volume.s There was a negative correlation between glutathione and neutrophils and monocytes whereas a positive correlation was found between malondialdehyde and the mean cell haemoglobin content, total white blood cell, monocyte, eosinophil, and basophil count. According to the findings of this study, pregnant women’s haematological parameters may be affected by oxidative stress.